Chapter The Land Cover/Use Code of the new Istat Census cartography - Mugnoli, Stefano (Proceedings e report, 2023)
ISTAT census layers, realized by ISTAT since 1991, are in update; this kind of digital cartography divides the entire national territory in very small enumeration areas to which are linked all the variables gathered during the census surveys. This layer, thanks to the several pieces of information related to each enumeration area, has a huge value for the statistical description of the Italian situation also regarding land cover and land use themes. Therefore, to further enrich the information assets of the ISTAT cartography, Environment and Territory Service of the Institute aims to produce an implementation of the enumeration areas layer to homogenise them with regard their land cover and land use. In addition, this is achieved through a specific code (Cod_TIPO_S) that can be related to the European frame LUCAS (Land Use and Cover Area Survey) legend. LUCAS survey represents the official frame for the dissemination of land cover and use statistics at continental level. For our purpose a specific transcoding table has been created between COD_TIPO_S and LUCAS legend. New enumeration areas layer provides for 47 legend entries In this brief paper both the work carried out and some provisional results for some of the major Italian urban areas are illustrated. The activities are in progress and are based on GIS algorithm and Python scripts.